TINDAK ILOKUSI DALAM KONFERENSI PERS DONALD TRUMP PADA PERTEMUAN KOREA UTARA-AMERIKA SERIKAT TAHUN 2018 DI SINGAPURA - Tallulembang, Romaryo Tomby; Lasut, Theresia M.C; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Romaryo Tomby Tallulembang1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Dra. Theresia M. C. Lasut, M.Hum2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Dr. Garryn C. Ranuntu, S.Pd., M.Hum3Â  Â  Â  Â  Â This research entitled â€œIllocutionary Act of Donald Trumpâ€™s Press Conference on 2018 North Korea-United States Singapore Summitâ€ is a pragmatic analysis focusing on speech act, especially, illocutionary act. This research is an attempt to indentify and classify types and analyze and describe functions of illocutionary act used by Donald Trump during the press conference. This research is conducted by using descriptive method where the focus on this research is identifying illocutionary acts on the press conference. Furthermore, this research is done by using theory from Austin (1962) to analyze and classify those illocutionary acts according its function. The result of this research shows that there are 66 illocutionary acts found on the press conference and all the data are divided into five types of illocutionary acts and its function, such as: verdictives (find as a matter of fact, calculate, estimate, describe, hold as a matter of fact, and value), ecersitives (appoint, proclaim, name, order, nominate, advice, grant, choose, and bequeath), commissives (promise, declare my intention, contract, undertake, oppose, and espouse), behabitives (compliment, apologize, and thank), expositives (give a view and give a statement)._ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _Keywords: Pragmatic, Illocutionary Act, Donald Trump, Press Conference